Preparação e Modificação Química de Nanoestruturas de Octa(aminopropil) silsesquioxano para Aplicações Analíticas - Magossi, Mariana de Souza [UNESP] (2015)
In this work, the novel compounds based silsesquioxane copper nitroprusside and nickel nitroprusside were prepared starting from octa(aminopropyl)silsesquioxane following a new synthesis route. The composites prepared as described ACCuN and ACNiN were preliminarily characterized by spectroscopic techniques, such Fourier Transform- Infrared Spectroscopy (FTIR), Scanning Electron Microscopy coupled with Energy X-Ray (SEM- EDS), Transmission Electron Microscopy (TEM), Nuclear Magnetic Resonance (NMR), X- ray Diffraction (XRD), Thermogravimetric Analysis (TG), Diffuse Reflectance UV/Vis, and study of the voltammetric behavior through electrochemical techniques such as cyclic voltammetry (CV), square wave voltammetry (SWV) and differential pulse voltammetry (DPV). The FTIR spectra showed absorption bands at 1106 cm -1 due to symmetric stretching Si-O-Si (Si-O-Si) characteristic of the structure of octa(aminopropyl)silsesquioxane and absorption bands at 2063 cm -1 ascribed to stratching (NO) and 2192 cm -1 attributed to C≡N (C≡N) . SEM and EDS observed clusters of cubic particles with an average size of approximately 241 nm and 265 nm, containing Si, O, N, Cu, Ni and Fe. The cyclic voltammetry of carbon paste electrode with ACCuN and ACNiN presented a good electrochemical stability, excellent reproducibility, and a redox pair with a formal potential (E θ ' ) = 0.73 V and 0.54 V (vs Ag/AgCl (sat.) ) assigned to the redox couple Fe (II) (CN) 5 NO/Fe (III) (CN) 5 NO, respectively (vs Ag/AgCl (sat.), KCl 1.0 mol L -1, pH = 7.0; v = 20mV s -1 ). The nanocomposite ACCuN was sensitive to concentration of L-cysteine, with a linear response 2.0 × 10 -4 to 2.0×10 -3 mol L -1 (R = 0.998), relative standard deviation of ± 2% (n = 3), to a limit of sensitivity of amperometric detection and 1.25×10 -4 mol L -1 and 10.66 mA / mol L -1, respectively for cyclic voltammetry. For differential pulse ...